Pengaruh Nilai-Nilai Politik Islam Terhadap Sikap Politik Pemuda Muslim di Kota Baubau - Junaid Gazalin; Siti Fahira; Aulia; Alan Noari; Ivarno Adibarta (SETYAKI : Jurnal Studi Keagamaan Islam, 2025)
This study examines the influence of Islamic political values ​​on the political attitudes of Muslim youth in Baubau City. Islamic political values ​​are a set of principles derived from Islamic teachings that emphasize justice, deliberation, equal rights, and trustworthiness in social and state life. This study used a qualitative approach with a literature review and descriptive analysis. The findings indicate that internalization of Islamic political values ​​contributes significantly to shaping the political attitudes of Muslim youth—particularly in terms of political participation, democratic orientation, and views on social and political norms. These values ​​also result in more inclusive, tolerant, and active political attitudes in national and state life